Chitosan-based modified membrane material as well as preparation method and application thereof
By adding quaternized chitosan to the polyvinylidene fluoride film material, the ion selective permeability is improved, and the problem of low power density and difficulty in large-area preparation of osmotic power generation film is solved, thus achieving high power density and easy access to Industrially prepared chitosan-based modified membrane material.
Patent Information
- Application Number
- CN202411670873.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-18
AI Technical Summary
In the prior art, the power density of the osmotic power generation film is low and difficult to prepare on a large scale.
By adding quaternized chitosan to the polyvinylidene fluoride film material to improve its ion selective permeability, a chitosan-based modified film material was prepared. The process includes mixing quaternized chitosan with polyvinylidene fluoride in an organic solvent and drying on the matrix material.
It has achieved the preparation of flexible films with high power density. The film has selective permeability to ions, is suitable for osmotic energy generation, and is simple in preparation and is easy to be prepared on a large scale.
Smart Images

Figure CN119455699A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer material preparation, and in particular to a chitosan-based modified membrane material and a preparation method and application thereof. Background Art
[0002] Self-generation technology through membrane ion rectification characteristics is an emerging electrochemical energy conversion technology that relies on the migration of ions through the membrane in an asymmetric environment to generate a potential difference. The core principle of this technology is that when ions pass through a membrane with ion rectification characteristics in solutions of different concentrations, a directional ion flow is generated, thereby driving the electron flow and realizing energy conversion. This type of technology is usually similar to the ion transport mechanism in organisms, especially the ion channels and nanopore structures in biological membranes. With the development of nanotechnology, materials science and electrochemical technology, self-generation technology with ion rectification characteristics will continue to improve its energy conversion efficiency and become an important research direction in the field of green energy and micro energy in the future. Common preparation methods include chemical etching, ion beam engraving, template method, electrochemical etching, etc., but nanochannels are difficult to prepare on a large scale due to their small size, difficulty in regulation and complex preparation process. Summary of the invention
[0003] In view of the problem that the power density of the osmotic pressure power generation film produced by the prior art is low and it is difficult to prepare it on a large scale, the present invention provides a chitosan-based modified membrane material and a preparation method and application thereof.
[0004] To achieve the above object, the present invention provides the following solutions: One of the technical solutions of the present invention is a method for improving the ion selective permeability of a polyvinylidene fluoride membrane material, which improves the ion selective permeability of the polyvinylidene fluoride membrane material by adding quaternized chitosan to the polyvinylidene fluoride membrane material; The mass ratio of the quaternized chitosan to the polyvinylidene fluoride is (3-7):3.
[0005] In a preferred embodiment of the present invention, the method for improving the ion selective permeability of the polyvinylidene fluoride membrane material comprises the following steps: The quaternized chitosan and polyvinylidene fluoride are added into an organic solvent and mixed to obtain a solution; The solution was poured onto the base material and dried.
[0006] In a preferred embodiment of the present invention, the organic solvent is N-methyl-2-pyrrolidone; the drying temperature is 80-85° C., and the drying time is 18-24 hours.
[0007] In a preferred embodiment of the present invention, the quaternization degree of the quaternized chitosan is 10%-40%.
[0008] In a preferred embodiment of the present invention, the method for preparing quaternized chitosan comprises the following steps: mixing chitosan with dimethyl sulfate and water to obtain a suspension; NaOH and NaCl are added to the suspension to carry out condensation reflux reaction to obtain the quaternized chitosan.
[0009] In a preferred embodiment of the present invention, the mass volume ratio of the chitosan to the dimethyl sulfate and water is 1 g:16 mL:4 mL.
[0010] In a preferred embodiment of the present invention, the temperature of the condensation reflux reaction is 70-75° C. and the time is 3-12 h.
[0011] The second technical solution of the present invention is a chitosan-based modified membrane material, which is prepared by the above-mentioned method for improving the ion selective permeability of polyvinylidene fluoride membrane material.
[0012] The third technical solution of the present invention is the application of the above-mentioned chitosan-based modified membrane material in osmotic energy power generation.
[0013] The present invention discloses the following technical effects: The preparation method of the invention is simple and easy to be prepared on a large scale in an industrial manner.
[0014] The method of the present invention can be used to prepare a flexible film (i.e., a chitosan-based modified membrane material) with high power density. The film has selective permeability to ions, similar to a solid diode, and the film thickness is between 0.08 and 0.11 mm. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0016] Figure 1 This is a SEM image of the QCS-3 sample prepared in step (5) of Example 1 of the present invention; Figure 2 This is a cross-sectional SEM image of the QCS-3 membrane prepared in Example 1 of the present invention; Figure 3 This is a diagram of the device for testing the ion rectification performance of the QCS-3 membrane prepared in Example 1 of the present invention; Figure 4 This is a graph showing the ion rectification performance test results of the QCS-3 membrane prepared in Example 1 of the present invention; Figure 5 This is a graph showing the test results of the ion rectification performance of the QCS membrane (chitosan-based modified membrane material) prepared in Examples 1-5 of the present invention; Figure 6 This is a test diagram of the concentration difference output power density and current density of the QCS-3 membrane prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0017] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0018] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0019] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0020] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0021] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0022] The "%" described in the present invention, unless otherwise specified, refers to mass percentage.
[0023] One of the technical solutions of the present invention is a method for improving the ion selective permeability of a polyvinylidene fluoride membrane material, which improves the ion selective permeability of the polyvinylidene fluoride membrane material by adding quaternized chitosan to the polyvinylidene fluoride membrane material; The mass ratio of the quaternized chitosan to the polyvinylidene fluoride is (3-7):3.
[0024] Chitosan is a natural bioactive substance that is considered to be a preferred material due to its non-toxicity, biocompatibility and low cost. The present invention provides a chitosan modified membrane material. Chitosan contains a free amino group (-NH2) in its structure, which itself has a pair of lone electron pairs. After -NH2 is quaternized, the N atom in -NH2 becomes -N + (CH3)3 ions are more likely to interact electrostatically with anions in solution, building ion transmission channels with asymmetric charges in the membrane structure, thereby making the chitosan-based modified membrane material (QCS) membrane have higher concentration output power density and current density.
[0025] The present invention uses a condensation reflux method to prepare quaternized chitosan. After the chitosan is quaternized, its water solubility is greatly improved, and the internal tubular structure is more convenient for ion transmission, so that the QCS membrane has a high concentration difference output power density and current density, which is more conducive to its application in osmotic energy power generation.
[0026] If the amount of quaternized chitosan used is too much, the quaternized sample will not be completely cross-linked, and a powder sample will remain after drying; if the amount of quaternized chitosan used is too little, the performance of the prepared membrane will be reduced.
[0027] In a preferred embodiment of the present invention, the method for improving the ion selective permeability of the polyvinylidene fluoride membrane material comprises the following steps: The quaternized chitosan and polyvinylidene fluoride are added into an organic solvent and mixed to obtain a solution; The solution was poured onto the base material and dried.
[0028] In a preferred embodiment of the present invention, the organic solvent is N-methyl-2-pyrrolidone; the drying temperature is 80-85° C., and the drying time is 18-24 hours.
[0029] The present invention does not impose any particular limitation on the amount of the organic solvent used. The amount of the organic solvent used is sufficient to fully dissolve the quaternized chitosan and the polyvinylidene fluoride.
[0030] In a preferred embodiment of the present invention, the quaternization degree of the quaternized chitosan is 10%-40%.
[0031] As the quaternization degree of quaternized chitosan increases, the ion selectivity of the prepared chitosan-based modified membrane material increases. The highest quaternization degree of the sample prepared by the present invention is 38.6%.
[0032] In a preferred embodiment of the present invention, the method for preparing quaternized chitosan comprises the following steps: mixing chitosan with dimethyl sulfate and water to obtain a suspension; NaOH and NaCl are added to the suspension to carry out condensation reflux reaction to obtain the quaternized chitosan.
[0033] In a preferred embodiment of the present invention, the mass volume ratio of the chitosan to the dimethyl sulfate and water is 1 g:16 mL:4 mL.
[0034] In a preferred embodiment of the present invention, the temperature of the condensation reflux reaction is 70-75° C., and the time is 3-12 h, specifically 3 h, 5 h, 8 h, 10 h and 12 h.
[0035] After the condensation reflux reaction is completed, the step of washing with 95% ethanol solution and drying at 80-85° C. for 12-14 hours is also included.
[0036] The quaternized chitosan obtained through commercial channels is also suitable for the present invention; the reason for making the quaternized chitosan in the present invention is to explore the influence of different quaternization degrees on the performance of chitosan-based modified membrane materials.
[0037] The second technical solution of the present invention is a chitosan-based modified membrane material, which is prepared by the above-mentioned method for improving the ion selective permeability of polyvinylidene fluoride membrane material.
[0038] The third technical solution of the present invention is the application of the above-mentioned chitosan-based modified membrane material in osmotic energy power generation.
[0039] The technical solutions described in the present invention, unless otherwise specified, are all conventional solutions in the art, and the reagents or raw materials used, unless otherwise specified, are purchased from commercial channels or have been disclosed.
[0040] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0041] Example 1 This embodiment provides a method for preparing a chitosan-based modified membrane material (QCS film), the steps are as follows: (1) Weigh 2 g of chitosan and add it to a mixed solution of 32 mL of dimethyl sulfate (DMS) and 8 mL of water to obtain a suspension.
[0042] (2) Transfer the suspension from step (1) into a round-bottom flask.
[0043] (3) Heat the round-bottom flask in a water bath for condensation reflux reaction, and set the reaction temperature to 70°C.
[0044] (4) When the water bath temperature reached 70°C, 2.4 g of NaOH and 1.76 g of NaCl powder were weighed and added into the round-bottom flask and the reaction was continued for 3 h.
[0045] (5) The reacted sample was washed with 95% ethanol solution and dried in a drying oven at 80 °C for 12 h to obtain a quaternized chitosan (QCS) sample. The quaternization degree of chitosan was calculated to be 16.3%.
[0046] (6) Weigh 0.7 g of dried quaternized chitosan (QCS) sample and 0.3 g of polyvinylidene fluoride (PVDF) into 15 mL of N-methyl-2-pyrrolidone and stir until the mixture is well mixed.
[0047] (7) The uniformly stirred solution was poured onto a smooth glass surface dish, placed in a drying oven, and dried at 80° C. for 24 h to obtain a quaternized chitosan (QCS) film.
[0048] (8) The dried film was peeled off from the glass dish to obtain a complete film with a high power density, which was named QCS-3 film and had a thickness of 0.093 mm.
[0049] Example 2 This embodiment provides a method for preparing a chitosan-based modified membrane material (QCS film), the steps are as follows: (1) Weigh 2 g of chitosan and add it to a mixed solution of 32 mL of DMS and 8 mL of water to obtain a suspension.
[0050] (2) Transfer the suspension from step (1) into a round-bottom flask.
[0051] (3) Heat the round-bottom flask in a water bath for condensation reflux reaction, and set the reaction temperature to 70°C.
[0052] (4) When the water bath temperature reached 70°C, weigh 2.4 g of NaOH and 1.76 g of NaCl powder, add them into the round-bottom flask and continue the reaction for 5 h.
[0053] (5) The reacted sample was washed with 95% ethanol solution and dried in a drying oven at 80 °C for 12 h to obtain a quaternized chitosan (QCS) sample. The quaternization degree of chitosan was calculated to be 22.4%.
[0054] (6) Weigh 0.7 g of dried quaternized chitosan (QCS) sample and 0.3 g of polyvinylidene fluoride (PVDF) into 15 mL of N-methyl-2-pyrrolidone and stir until the mixture is well mixed.
[0055] (7) The uniformly stirred solution was poured onto a smooth glass surface dish, placed in a drying oven, and dried at 80° C. for 24 h to obtain a quaternized chitosan (QCS) film.
[0056] (8) The dried film was peeled off from the glass dish to obtain a complete film with a high power density, which was denoted as QCS-5 film and had a thickness of 0.086 mm.
[0057] Example 3 This embodiment provides a method for preparing a chitosan-based modified membrane material (QCS film), the steps are as follows: (1) Weigh 2 g of chitosan and add it to a mixed solution of 32 mL of DMS and 8 mL of water to obtain a suspension.
[0058] (2) Transfer the suspension from step (1) into a round-bottom flask.
[0059] (3) Heat the round-bottom flask in a water bath for condensation reflux reaction, and set the reaction temperature to 70°C.
[0060] (4) When the water bath temperature reached 70°C, weigh 2.4 g of NaOH and 1.76 g of NaCl powder, add them into the round-bottom flask and continue the reaction for 8 h.
[0061] (5) The reacted sample was washed with 95% ethanol solution and dried in a drying oven at 80 °C for 12 h to obtain a quaternized chitosan (QCS) sample. The quaternization degree of chitosan was calculated to be 38.6%.
[0062] (6) Weigh 0.7 g of dried quaternized chitosan (QCS) sample and 0.3 g of polyvinylidene fluoride (PVDF) into 15 mL of N-methyl-2-pyrrolidone and stir until the mixture is well mixed.
[0063] (7) The uniformly stirred solution was poured onto a smooth glass surface dish, placed in a drying oven, and dried at 80° C. for 24 h to obtain a quaternized chitosan (QCS) film.
[0064] (8) The dried film was peeled off from the glass dish to obtain a complete film with a high power density, which was denoted as QCS-8 film and had a thickness of 0.092 mm.
[0065] Example 4 This embodiment provides a method for preparing a chitosan-based modified membrane material (QCS film), the steps are as follows: (1) Weigh 2 g of chitosan and add it into a mixed solution of 32 mL of DMS and 8 mL of water.
[0066] (2) Transfer the suspension from step (1) into a round-bottom flask.
[0067] (3) Heat the round-bottom flask in a water bath for condensation reflux reaction, and set the reaction temperature to 70°C.
[0068] (4) When the water bath temperature reaches 70°C, weigh 2.4 g of NaOH and 1.76 g of NaCl powder, add them into the round-bottom flask and continue the reaction for 10 h.
[0069] (5) The reacted sample was washed with 95% ethanol solution and dried in a drying oven at 80 °C for 12 h to obtain a quaternized chitosan (QCS) sample. The quaternization degree of chitosan was calculated to be 24.7%.
[0070] (6) Weigh 0.7 g of dried quaternized chitosan (QCS) sample and 0.3 g of polyvinylidene fluoride (PVDF) into 15 mL of N-methyl-2-pyrrolidone and stir until the mixture is well mixed.
[0071] (7) The uniformly stirred solution was poured onto a smooth glass surface dish, placed in a drying oven, and dried at 80° C. for 24 h to obtain a quaternized chitosan (QCS) film.
[0072] (8) The dried film was peeled off from the glass dish to obtain a complete film with a high power density, which was denoted as QCS-10 film and had a thickness of 0.107 mm.
[0073] Example 5 This embodiment provides a method for preparing a chitosan-based modified membrane material (QCS film), the steps are as follows: (1) Weigh 2 g of chitosan and add it into a mixed solution of 32 mL of DMS and 8 mL of water.
[0074] (2) Transfer the suspension from step (1) into a round-bottom flask.
[0075] (3) Heat the round-bottom flask in a water bath for condensation reflux reaction, and set the reaction temperature to 70°C.
[0076] (4) When the water bath temperature reached 70°C, weigh 2.4 g of NaOH and 1.76 g of NaCl powder, add them into the round-bottom flask and continue the reaction for 12 h.
[0077] (5) The reacted sample was washed with 95% ethanol solution and dried in a drying oven at 80 °C for 12 h to obtain a quaternized chitosan (QCS) sample. The quaternization degree of chitosan was calculated to be 18.6%.
[0078] (6) Weigh 0.7 g of dried quaternized chitosan (QCS) sample and 0.3 g of polyvinylidene fluoride (PVDF) into 15 mL of N-methyl-2-pyrrolidone and stir until the mixture is well mixed.
[0079] (7) The uniformly stirred solution was poured onto a smooth glass surface dish, placed in a drying oven, and dried at 80° C. for 24 h to obtain a quaternized chitosan (QCS) film.
[0080] (8) The dried film was peeled off from the glass dish to obtain a complete film with a high power density, which was denoted as QCS-12 film and had a thickness of 0.104 mm.
[0081] The QCS-3 film obtained in Example 1 was characterized in morphology, and its rectification effect and power density were tested. The test results are as follows: 1. Morphological characterization of quaternized chitosan: Figure 1 This is a SEM image of the QCS-3 sample prepared in step (5) of Example 1 of the present invention. Figure 1 It can be seen that the quaternized chitosan is in the shape of a rod.
[0082] Figure 2 This is a cross-sectional SEM image of the QCS-3 membrane prepared in Example 1 of the present invention. Figure 2 It can be seen that the chitosan-based modified membrane material has an irregular pore structure.
[0083] 2. Ion rectification performance test: Figure 3 This is a diagram of the device for testing the ion rectification performance of the QCS-3 membrane prepared in Example 1 of the present invention: Figure 4 This is a graph showing the ion rectification performance test results of the QCS-3 membrane prepared in Example 1 of the present invention.
[0084] like Figure 3 The film shown is fixed in the middle of an H-type electrolytic cell, and sodium chloride solutions of the same concentration are added to the electrolytic cells on both sides to test the transmembrane transport of ions in sodium chloride solutions of different concentrations (0.1mM, 0.3mM, 0.5mM, 0.7mM, 1.0mM). Using an electrochemical workstation, cyclic voltammetry was used to test the four-electrode system, with platinum wire as the working electrode and counter electrode, silver / silver chloride electrode as the sensing electrode and reference electrode, the voltage window selected between -0.6 and +0.6, the scanning speed was 50mV / s, and the nonlinear current-voltage curve was measured.
[0085] Depend on Figure 4It can be seen that the current under negative voltage is significantly greater than the current under positive voltage. By calculating the absolute value ratio of positive and negative currents, the ion selectivity of quaternized chitosan is evaluated (the larger the absolute value ratio of positive and negative currents, the better the ion selectivity). Figure 4 It can be seen that with the increase of electrolyte concentration, the ion selectivity of quaternized chitosan membrane improves.
[0086] Figure 5 The ion rectification performance test results of the QCS membrane prepared in Examples 1-5 of the present invention are shown in FIG. Figure 5 It can be seen that at the same concentration, QCS-8 has the best ion selectivity. Since the quaternization degree of QCS-8 membrane is the highest, it can be shown that the higher the quaternization degree, the better the ion selectivity of the membrane.
[0087] 3. Power density test Figure 6 This is a test diagram of the concentration difference output power density (Power density) and current density (Current density) of the QCS-3 membrane prepared in Example 1 of the present invention, wherein the ordinate on the left represents the output current density, the ordinate on the right represents the output power density, and the abscissa represents the external resistance, wherein the concentration difference of the sodium chloride solution in the left and right electrolytic cells is 1:50 (0.01M / 0.5M).
[0088] Depend on Figure 5 It can be clearly seen that the QCS-3 membrane has a high output power density, which can reach 4.2W / m at a concentration difference of 50 times. 2 .
[0089] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for improving the ion selective permeability of a polyvinylidene fluoride membrane material, characterized in that: The ion selective permeability of polyvinylidene fluoride membrane material is improved by adding quaternized chitosan into the polyvinylidene fluoride membrane material; The mass ratio of the quaternized chitosan to the polyvinylidene fluoride is (3-7):
3.
2. The method for improving the ion selective permeability of polyvinylidene fluoride membrane material according to claim 1, characterized in that: The following steps are involved: The quaternized chitosan and polyvinylidene fluoride are added into an organic solvent and mixed to obtain a solution; The solution was poured onto the base material and dried.
3. The method for improving the ion selective permeability of polyvinylidene fluoride membrane material according to claim 2, characterized in that: The organic solvent is N-methyl-2-pyrrolidone; the drying temperature is 80-85° C. and the drying time is 18-24 hours.
4. The method for improving the ion selective permeability of polyvinylidene fluoride membrane material according to claim 1, characterized in that: The quaternization degree of the quaternized chitosan is 10%-40%.
5. The method for improving the ion selective permeability of polyvinylidene fluoride membrane material according to claim 1, characterized in that: The preparation method of the quaternized chitosan comprises the following steps: mixing chitosan with dimethyl sulfate and water to obtain a suspension; NaOH and NaCl are added to the suspension to carry out condensation reflux reaction to obtain the quaternized chitosan.
6. The method for improving the ion selective permeability of polyvinylidene fluoride membrane material according to claim 5, characterized in that: The mass volume ratio of the chitosan to the dimethyl sulfate and water is 1 g:16 mL:4 mL.
7. The method for improving the ion selective permeability of polyvinylidene fluoride membrane material according to claim 5, characterized in that: The temperature of the condensation reflux reaction is 70-75° C. and the time is 3-12 hours.
8. A chitosan-based modified membrane material, characterized in that: The method for improving the ion selective permeability of polyvinylidene fluoride membrane materials according to any one of claims 1 to 7 is used to prepare the polyvinylidene fluoride membrane material.
9. Use of the chitosan-based modified membrane material as claimed in claim 8 in osmotic energy power generation.